OP0316 Duration of clinical remission and flare rates in patients with juvenile idiopathic arthritis after withdrawal of biological treatment (preliminary data). (15th June 2017) - Kashchenko, E; Alexeeva, E; Bzarova, T; Valieva, S; Isaeva, K; Denisova, R; Lomakina, O; Sleptsova, T; Soloshenko, M; Karaseva, A
Abstract : Background: Prolonged therapy with biological agents (BAs) may cause adverse events, which leads to the necessity of discontinuation of BAs in patients with juvenile idiopathic arthritis (JIA), once complete disease quiescence has been achieved. Objectives: To estimate the length of time in clinical remission and time to disease flare after discontinuation of treatment with BAs. Methods: 83 patients with JIA (33 – with systemic onset, 50 – with oligo- or polyarticular arthritis) were included in the survey. The cohort was 34, 9% (29 patients) male and 65, 1% (54 patients) female with a mean age of 11±3, 69 years (range 5–17 years). All patients with systemic JIA (sJIA) were treated with tocilizumab, 35 (70%) patients with other types of JIA received etanercept, 15 (30%) – adalimumab. 14 (42, 4%) patients with sJIA additionally got methotrexate, 5 (15, 1%) – cyclosporine, 5 (15, 1%) – glucocorticoids, 1 (3, 0%) – leflunomide; 9 (25, 7%) and 7 (46, 6%) patients took combination therapy of etanercept or adalimumab and methotrexate. Patients were randomized into 2 main groups using envelope method: in a first group a BA was discontinued abruptly, while in the second it was tapered gradually by increasing injection/infusion interval. Results: Duration of inactive disease/clinical remission during tocilizumab treatment was 43±12, 16/37±12, 16 months, etanercept – 40±13, 13/34±13, 17 months, adalimumab – 48±11, 9/40±12, 06 months. Tocilizumab, etanercept, adalimumab were discontinued in 22 (66, 6%), 28 (80, 0%), 11 (73, 3%) patients and were tapered by increasing injection/infusion interval in 11 (33, 4%), 7 (20, 0%), 4 (26, 7%) cases, respectively. After withdrawal of tocilizumab, etanercept and adalimumab 29 (87, 9%), 24 (68, 6%), 6 (40, 0%) patients remained in remission of JIA for 6±10, 23 (1–48) months, 6±5, 07 (1–20) months and 6±13, 33 (4–38) months, respectively. 4 (12, 1%), 11 (31, 4%), 9 (60, 0%) patients flared within 8±5, 65 (6–18) months, 5, 5±3, 49 (1, 5–12) months and 4±4, 64 (1–13) months after discontinuation of tocilizumab, etanercept and adalimumab, respectively. Conclusions: Withdrawal of BAs after clinical remission for more than 1, 5 years was not associated with a disease exacerbation in more than 70% of patients with JIA. A mean duration of clinical remission after withdrawal of BAs was 6 months. Disclosure of Interest: E. Kashchenko Grant/research support from: Novartis, E. Alexeeva Grant/research support from: Roche, Abbott, Pfizer, Bristol-Myers Squibb, Centocor, Novartis, Speakers bureau: Roche, Merck Sharp & Dohme, Abbott, Bristol-Myers Squibb, Medac, Novartis, Pfizer, T. Bzarova Grant/research support from: Roche, Pfizer, Novartis, Speakers bureau: Roche, Merck Sharp & Dohme, Abbott, Pfizer, S. Valieva Grant/research support from: Roche, Bristol-Myers Squibb, Speakers bureau: Roche, Merck Sharp & Dohme, Bristol-Myers Squibb, Medac, Novartis, K. Isaeva Grant/research support from: Roche, Novartis, R. Denisova Grant/research support from: Roche, Centocor, Novartis, Speakers bureau: Roche, Merck Sharp & Dohme, Abbott, Medac, O. Lomakina: None declared, T. Sleptsova Grant/research support from: Centocor, Speakers bureau: Merck Sharp & Dohme, Bristol-Myers Squibb, M. Soloshenko: None declared, A. Karaseva: None declared